Heterologous Overexpression and Functional Analysis of the Isodon suzhouensis IsKS1 Gene in Arabidopsis thaliana - Fawang Liu; Kefeng Zhai; Dongmei Xie (Current Issues in Molecular Biology, 2025)
Isodon suzhouensis, also known as “Wangzaozi”, is an edible and medicinal plant belonging to the Lamiaceae family. Its main functional constituents are the tetracyclic diterpenoids known as wangzaozins. Wangzaozins have a strong structural similarity to gibberellins (GAs), which are synthesized via the diterpenoid biosynthetic pathway (map00904). The formation of the diterpenoid skeleton is regulated by copalyl diphosphate synthase (CPS) and kaurene synthase (KS). In order to identify and study the KS gene involved in wangzaozins biosynthesis, a transcriptomic and metabolomic analysis of Isodon suzhouensis was performed. The IsKS1 gene, which was highly expressed in leaves, was successfully cloned. The binding mode and sites of IsKS1 with its catalyzed substrate, ent-copalyl diphosphate (ent-CPP), were predicted using AutoDock. The docking results revealed hydrophobic interactions, hydrogen bonds, and salt bridges between them. Furthermore, overexpression of IsKS1 in Arabidopsis thaliana resulted in a significant increase in gibberellin content, as well as the up-regulation of GA2(KS) and GA3OX1 genes. These results suggest that the IsKS1 gene is involved in gibberellin biosynthesis and may potentially contribute to the biosynthesis of wangzaozins.